PENGARUH PELATIHAN TERHADAP KINERJA KARYAWAN DIMODERASI OLEH LINGKUNGAN KERJA - Tiara Ajeng Meilani; Islamuddin Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the effect of training on employee performance, moderation by the work environment, among employees of CV Yahyo (a palm oil seed producer). This research is quantitative, using an explanatory approach. The population was all employees of CV Yahyo (a palm oil seed producer). The total sampling method was used, comprising all 70 employees of CV Yahyo (a palm oil seed producer). Data collection techniques used were observation, documentation, and questionnaires. Data analysis techniques used were descriptive analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study show that training has a positive and significant effect on employee performance, the work environment has a positive effect on employee performance, and the work environment weakens the relationship between training and employee performance. Keywords : Training, Employee Performance, and Work Environment.